Pengaruh Investasi Dan Indeks Pembangunan Manusia Terhadap Pertumbuhan Ekonomi Regional Di Provinsi Kalimantan Utara - Imelda Sari (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2022)
Economic growth in North Kalimantan Province, the youngest province in Indonesia, is influenced by other economic variables. This study is a quantitative study supported by a descriptive explanation, with the aim of looking at the effect of investment and the human development index on regional economic growth in North Kalimantan Province, referring to 2013-2020 data. The analytical method used is multiple linear regression analysis method using SPSS version 20. Simultaneously investment and HDI have a significant effect on economic growth in North Kalimantan Province, meaning that the greater the investment value along with the better human development related to the Human Development Index, then economic growth in North Kalimantan Province will increase. Partially, investment has a positive and insignificant effect on economic growth in North Kalimantan Province. This situation indicates that investment has not been able to maximize or increase economic growth because investment has not been evenly distributed in all sectors, so that economic growth has increased but not significantly. Partially, the Human Development Index (HDI) has a positive and significant effect on economic growth in North Kalimantan Province. A high level of HDI achievement plays an important role in increasing economic growth in North Kalimantan Province.